2022
DOI: 10.1109/lmwc.2022.3154060
|View full text |Cite
|
Sign up to set email alerts
|

Peak Power Handling Capability in Groove Gap Waveguide Filters Based on Horizontally Polarized Resonators and Enhancement Solutions

Abstract: This letter studies the peak power handling capability (PPHC) in groove gap waveguide filters based on horizontally polarized resonators. Moreover, a modification of the resonant cavity is proposed, where the central pins of the original structure are replaced by a rounded metal block. As a result of this change, the TE 101 -like mode can still be excited, but the maximum electric field strength is shifted to the center of the cavity, which leads to a higher PPHC. The main advantages of the original structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Table 5 compares various GGW bandpass filters with the wideband GGW Chebyshev filters manufactured in this work. The order n or number of cells of the GGW filters [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] reported in Table 5 varies between two and seven, and almost half of them are of order five, as are the proposed GGW filters. The structures were mainly manufactured by means of a CNC milling machine, except for two [36,41] that also used a 3D printing technique.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 5 compares various GGW bandpass filters with the wideband GGW Chebyshev filters manufactured in this work. The order n or number of cells of the GGW filters [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] reported in Table 5 varies between two and seven, and almost half of them are of order five, as are the proposed GGW filters. The structures were mainly manufactured by means of a CNC milling machine, except for two [36,41] that also used a 3D printing technique.…”
Section: Resultsmentioning
confidence: 99%
“…Half of them are distributed in the low X and Ku bands (8 GHz-18 GHz) as the proposed design. As can be seen in Table 5, unlike the proposed design method and [45], which can achieve wideband responses (FBW > 10%), the other filters developed are narrowband (FBW < 4%), since they were obtained from resonant cavities [30][31][32][33][34][35][36], coupled resonators [37][38][39][40][41][42], evanescent wave coupled resonators [43], and periodic corrugations acting as resonators [44], which can only work in a narrow bandwidth. The wideband response of the proposed GGW bandpass filter design was obtained by combining the high-pass behavior of the GGW with the low-pass characteristic of the metallic pins placed along the groove area of the GGW, acting as impedance inverters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to previous research related to the corona discharge breakdown thresholds in GW technology, a preliminary study based on simulations for guided structures can be found in [42], where measured results are not presented. Moreover, a strategy for enhancing the PPHC in horizontally polarized BPFs has been proposed in [43], where a measured improvement of 8.7 dB in the high-pressure range has been demonstrated. Also, other recent trends can be highlighted in the area of the corona discharge breakdown in microwaves, such as those where some novel numerical approaches have been studied [44], [45].…”
Section: Introductionmentioning
confidence: 99%